Acupuncture for mild cognitive impairment in elderly people: Systematic review and meta-analyses. Issue 39 (25th September 2020) - Li, Weitong; Wang, Qing; Du, Shizheng; Pu, Yalou; Xu, Guihua
Abstract: Background: Acupuncture has an unique role in preventing and managing mild cognitive impairment (MCI) in nonpharmaceutical therapies because of its small wound, mild pain, and high security for many years. However, there is no systematic review evaluating safety and efficacy of acupuncture for MCI in elderly people. Therefore, this study will provide a protocol to explore the effectiveness and safety of acupuncture for MCI in the elderly. Methods: Retrieval from 8 electronic databases was conducted to determine eligible trials published until May, 2019. Homogeneity qualified studies were included for data were extracted such as study country location, demographic characteristics, and measure outcomes, and were analyzed by a random effect model and sensitivity analyses to identify heterogeneity. Review Manager (Revman Version 5.3) software will be used for data synthesis, sensitivity analysis, meta regression, subgroup analysis, and risk of bias assessment. A funnel plot will be developed to evaluate reporting bias. Results: A total of 15 randomized control trials involving 1051 subjects were included. The results were as follows: Compared with the control group, the clinical efficacy rates of acupuncture was better, odds ratio = 2.52, 95% confidence interval (CI) (1.86, 3.42), P  < .00001, mini-mental state examination scores (mean difference [MD] = 1.53, 95% CI [1.04, 2.01], P  < .00001), Montreal cognitive assessment scores (MD = 2.05, 95% CI [1.17, 1.92], P  < .00001), activity of daily living scale (MD = 1.71, 95% CI [–1.38, 4.79], P  > .05), and clock drawing task scores (MD = 1.91, 95% CI [1.74, 2.08], P  < .00001). Conclusion: This study shows that acupuncture is beneficial for improving aspects of cognitive function in elderly people with MCI, which suggests that acupuncture may be an effective alternative and complementary approach to existing therapies for elderly people. More rigorous experimental studies and longer follow-up studies should be conducted in the future.